Polypoidal choroidal vasculopathy and systemic lupus erythematosus. (March 2014) - Chin, YC; Bhargava, M; Khor, CC; Cheung, CMG; Wong, TY
Systemic lupus erythematosus (SLE) associated with antiphospholipid syndrome can have ocular complications. We report a 44-year-old Chinese lady with recurrent relapses of SLE and antiphospholipid syndrome with high disease activity, presenting with visual distortion in her right eye for 2 months. There was subretinal hemorrhage in her right eye, confirmed on investigations to be choroidal neovascularization secondary to a variant of age-related macular degeneration known as polypoidal choroidal vasculopathy (PCV). Anti-vascular endothelial growth factor therapy resolved her eye condition. SLE could be associated with PCV via common mechanisms, including complement pathway activation and vasculitis involving the choroidal circulation.